A systematic approach to assess the effectiveness of airport noise mitigation strategies. (January 2016) - Postorino, Maria Nadia; Mantecchini, Luca
Abstract: Regional airports are often located very close to the urban area they serve and the increasing traffic rate that many of them have experienced in the last years has produced several impacts on the communities living close to the airport area, mainly aviation noise. If not properly managed, noise impacts produced by airport operations can cut down significantly the development of airport air traffic with direct effects on the economic and territorial systems. Aeronautical noise has greatly reduced in the last decade, due to aircraft design technological improvements and more severe regulations. However, the noise reduction during a single event does not make the issue of the airport location – and then the whole noise impact – less significant. This paper proposes an assessment process to evaluate the effects of actions adopted to reduce airport noise impacts on populated areas. Both airport-related factors – such as number of take-off; day-evening-night distributions of movements; aircraft type; flying paths – and land-use characteristics have been considered and combined in a density index that synthesizes the impacts of airport noise on the territory. The assessment process has been tested on a real case, the airport of Bologna in Northern Italy. The predicted results, compared with available real data for the test case, are significant and encourage the use of the proposed assessment process as decision support system for the airport management. Highlights: Airport aeronautical noise is one of the most relevant impacts of air transport. The noise impact relevance depends on both air transport and land-use variables. An assessment process to evaluate the effectiveness of actions to reduce airport noise is proposed. The Noise and Territory Overlap index synthesizes the airport noise impact on the territory. The application made to the real case of Bologna airport shows satisfactory results.